The Practice of Islamic Psychospiritual Therapy in the Treatment of Drug Addiction at Rehabilitation Centres in Malaysia - Zainal Abidin, M. Saiful Amri; M. Amin, M. Zohdi; Salaeh, Abdulloh; W. Yusoff, W. Fatimah Zahra’; Fa’atin, Salmah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
Drug addiction is a global problem and it also poses a threat to Malaysia. The Malaysian government through National Anti-Drug Agency (NADA) has implemented various approaches to eradicate drug abuse by providing rehabilitation centers and rehabilitation programs. Private institutions have also taken the same initiatives. One of the approaches in the recovery process used is Islamic psychospiritual therapy for Muslim addicts. However, the psychospiritual therapy program used varies and requires a holistic and comprehensive model. This study employed the qualitative approach through interviews with treatment center operators, observations of treatment center activities and text studies. It was conducted at several governments and private drug rehabilitation centers namely Cure & Care Rehabilitation Centre (CCRC) Tiang Dua, CCRC Sungai Ruan, Pondok Remaja Inabah Negeri Sembilan, Teratak Tautan Kaseh Murabbi and Persatuan Pengasih Malaysia. The study has revealed that Islamic psychospiritual therapy takes into account three main concepts and components that are tazkiyah al-nafs (soul purification), basic religious knowledge, and a therapeutic support system. Islamic psychospiritual therapy is found to help the government, private institutions and individuals to achieve the recovery of drug addicts especially in addressing the issue of relapse in drug addiction for Muslim addicts.